Highly stable and imperceptible electronics utilizing photoactivated heterogeneous sol-gel metal-oxide dielectrics and semiconductors - Jo, Jeong-Wan (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.